Assessment of metals (Ni, Ba) deposition in plant types and their organs at Mersin City, Türkiye - Koç, İsmail; Canturk, Ugur; Isinkaralar, Kaan; Ozel, Halil Baris; Sevik, Hakan (Springer Science and Business Media LLC, 2024)
The increase in heavy metal concentrations in the air, especially after the Industrial Revolution, is notable for the scientific world because of the adverse effects that threaten environmental and human health. Among the trace elements, nickel (Ni) is carcinogenic, and all barium (Ba) compounds are toxic. Trace elements are critical for human and environmental health. Their threat further increases, especially in the urban areas and surroundings with a high population. In urban areas, the trace element contamination in the airborne can be reduced using plants. However, which plant and plant organs absorb trace elements could not be determined. In the present study, Ni and Ba concentrations in the branch, wood, and leaf samples of 14 species collected from the city center of Mersin province were determined. As a result, broad-leaved species' Ni and Ba concentrations in their leaf sample were generally higher than other species. Almost all species had the lowest Ni and Ba concentrations in their wood samples. Among these 14 species, it was found that Ni concentration was very high, especially in non-washed leaves of Platanus orientalis, Photinia serrulata, and Citrus reticulate, and Ba concentration was very high in Citrus reticulata, Chamaecyparis lawsoniana, Laurus nobilis, and Acer hyrcanum. Using broad-leaved species in urban areas where pollution is at high levels will significantly contribute to reducing Ni and Ba pollution. It is recommended that these points be considered in future urban landscaping projects.
Keywords: Toxicity; Turkey; Air pollution; Urban air; Urban Air; Plants; Phytoremediation; Trace Elements; Heavy Metal; Heavy metal; Accumulation; Nickel; Air Pollution; Metals, Heavy; Humans; Traffic Density; Detoxification; Pb; Environmental Monitoring